A novel prototype design for a transformer for high voltage, high frequency, high power use. - Fothergill, J.C.
A prototype transformer has been designed and built which is novel in its combination of high voltage (50 kV), high frequency (20 kHz) and high power (25 kVA) specifications. The design technique utilized a spreadsheet approach which facilitated an iterative design procedure. The transformer used a ferrite core, nylon insulated secondary bobbins and pressurized sulfur hexafluoride encapsulation. It was designed as part of a high-voltage switched-mode power supply for driving electrostatic precipitators. The transformer was field tested at a large coal-fired power station and was found to have an efficiency of better than 98%
Keywords: 20 kHz; 25 kVA; 50 kV; AC-DC conversion; EHV transformers; HVDC insulation; Coal-fired power station; Efficiency; Electrostatic precipitators; Ferrite core; High frequency; High power; High voltage; High-voltage switched-mode power supply; Iterative design procedure; Nylon insulated secondary bobbins; Pressurized sulfur hexafluoride encapsulation; Spreadsheet; Transformer